Correction: Visible-light-mediated borylation of aryl and alkyl halides with a palladium complex. Issue 25 (17th June 2021) - Zhao, Jia-Hui; Zhou, Zhao-Zhao; Zhang, Yue; Su, Xuan; Chen, Xi-Meng; Liang, Yong-Min
Abstract : Correction for 'Visible-light-mediated borylation of aryl and alkyl halides with a palladium complex' by Jia-Hui Zhao, et al., Org. Biomol. Chem., 2020, 18, 4390–4394, DOI: ; 10.1039/D0OB00028K .